Pengaruh Pembelajaran â€œGuided Inquiry Small Researchâ€ Terhadap Keterampilan Proses Sains Siswa Pada Materi Bakteri Di SMA NU Juntinyuat - Sopwan, Indra Drajat; Sari, Yuli Arnita (Spizaetus: Jurnal Biologi dan Pendidikan Biologi, 2021)
This study aimed to analyze the The Effect of Learning Guided Inquiry Small Research Against Student Science Process Skills on Bacteria Material in Senior Hight School NU Juntinyuat. The method used Posttest-Only Control Design. The population in this study is the class X.1 and X.2 Senior High School NU Juntinyuat in 2019/2020 school year and totaling 52 students. Samplingwas done by using cluster random sampling, were divided into 2 groups: Guided Inquiry model class with 26 students and other class are not using Guided Inquiry as many as 26 students. Instruments in this research is the description of science process skills, observation sheets and questionnaires for students. Hypothesis test using parametric statistical tests in this case to test thehypothesis of The Effect of Learning Guided Inquiry Small Research models to enhance the critical thinking skills using Manova test was obtained p <0.05 is 0.042 <0.05, which means there is an increased The Effect of Learning "Guided Inquiry Small Research"of critical thinking skills of students.Kata Kunci: guided inquiry, science process skills